2017
DOI: 10.1016/j.jgr.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Melanogenesis inhibition activity of floralginsenoside A from Panax ginseng berry

Abstract: BackgroundPanax ginseng is a traditional herb used for medicinal purposes in eastern Asia. P. ginseng contains various ginsenosides with pharmacological effects. In this study, floralginsenoside A (FGA), ginsenoside Rd (GRD), and ginsenoside Re (GRE) were purified from P. ginseng berry.MethodsChemical structures of FGA, GRD, and GRE were determined based on spectroscopic methods, including fast atom bombardment mass spectroscopy, ID-nuclear magnetic resonance, and infrared spectroscopy. Inhibitory activities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…These compounds showed the minimum 10‐fold greater anti‐melanin deposition activities than arbutin. Reportedly, the melanogenesis inhibitory results of 6 , 8 , and 10 partially agreed to those of the previous studies, which concluded them as promising candidates for melanin inhibitors . The previous results demonstrated that 7 and 9 increased the melanin content in normal human melanocytes, while they showed the decrease of the activities against B16‐F10 mouse melanoma cells in this study .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…These compounds showed the minimum 10‐fold greater anti‐melanin deposition activities than arbutin. Reportedly, the melanogenesis inhibitory results of 6 , 8 , and 10 partially agreed to those of the previous studies, which concluded them as promising candidates for melanin inhibitors . The previous results demonstrated that 7 and 9 increased the melanin content in normal human melanocytes, while they showed the decrease of the activities against B16‐F10 mouse melanoma cells in this study .…”
Section: Resultssupporting
confidence: 89%
“…Many potent melanogenic inhibitors have been isolated from Ginseng . Several known depigmenting agents such as kojic acid, arbutin, resveratrol, niacinamide, tretinoin, and vitamin C have been used as both drugs and cosmetic formulations for hyperpigmentation disorders …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Panax ginseng is a medicinal herb, which contains various ginsenoside with therapeutic effects. Lee et al [63] isolated floralginsenoside (FGA), ginsenoside Rd. (GRd), and ginsenoside Re (GRe) from Panax ginseng berry.…”
Section: Inhibition Of Tyrosinase and Other Related Protein Expressionsmentioning
confidence: 99%
“…After MC1R activation, a series of intracellular signaling pathway composed of adenylyl cylase, its product, cAMP, and protein kinase A (PKA) participate in the activation of cAMP response element-binding (CREB) protein, and then microphthalmia-associated transcription factor (MITF) are sequentially expressed by CREB. Finally, synthesized MITF controls the expression of various genes such as tyrosinase, tyrosinase-related protein-1 (TRP)-1, and TRP-2 that are essential for melanin synthesis and secretion in melanocytes [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%